PENGARUH LEVERAGE, LIKUIDITAS, DAN PROFITABILITAS TERHADAP CASH HOLDING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2020 - Choriana Choriana; Rudy Rudy (JURNAL MITRA MANAJEMEN, 2023)
The purpose of this study was to determine the analysis of the effect of leverage, liquidity, and profitability on cash holding, either partially or simultaneously. Secondary data were collected from food and beverage companies listed on the Indonesia Stock Exchange for the 2015-2020 period and the journals of previous researchers. The method used is descriptive quantitative method. The sample was determined based on the purposive sampling method, as many as 78 samples of financial statements. The data used in this study is panel data (pooled data) which is a combination of time series data and cross section data. The data analysis method used in this study is a random effect model which is processed using Eviews 10. The results of this partial study indicate that Leverage (DAR) has a significant negative effect on cash holding (CH), Liquidity (CR) has a positive and insignificant effect on cash holding (CH), Profitability (ROA) has a significant negative effect on cash holding (CH). The results of Leverage (DAR), liquidity (CR) and profitability (ROA), together (simultaneously) have a significant effect on cash holding (CH). This is because the value of Prob. (F-statistic) 0.000022 is smaller than 0.05, and F-statistic is greater than Ftable (9.497463>2.73), with an influence value of 16.4933% while the remaining 83.5067% can be explained using other variables which were not investigated in this study.